How do future publication plans affect theses availability in UiT’s open access research archive? - Larssen, Tanja (Septentrio Conference Series, 2016)
Watch the VIDEO of the presentation. Open access to research results is a stated aim for the University of Tromsø – The artic university of Norway. The university’s research archive, Munin, has a well-developed system to make available the university’s own research, as well as master theses written by its students. Both master and PhD theses from UiT are delivered directly through Munin and can be made openly available on-line. Despite of this, many candidates choose not to have their theses made openly available through Munin. In my master thesis in document management, I examined why some candidates opt against, or postpone, making their theses openly available through Munin. What factors influence this decision, and are the given reasons based on actual issues or on misconceptions? From Munin I was given access to metadata from previously delivered, and passed, master and PhD theses where the candidate wanted to withhold their theses from being made openly available in Munin. The metadata contained the reasons provided by the candidates for their decision. I also conducted an electronic survey among, then, current master students where the goal was to examine current students’ attitudes towards making their thesis openly available in Munin, and compare the results from this survey with reasons stated by former master and PhD candidates. The main reason provided for postponing or refusing open access to their theses, given by both former master and PhD candidates, and current master students, where the fear that it would impair their chances for future publication. My study also showed that both master and PhD candidates from the faculty of health science are less likely to make their theses openly available in Munin, than candidates from other faculties. This faculty also had more candidates than other expressing concern over the possibilities for future publication. Why do candidates from different faculties within the same university show different attitudes towards having their work openly available? Are candidates right in their concerns regarding open availability and future publication, or are these concerns based on unfounded fears? Does it matter if master and PhD candidates choses not to make their work openly available, and can candidates be encouraged to make their work available?